A cidade e o clima: impactos das precipitações concentradas e as tendências climáticas em Uberlândia-MG - Silva, Emerson Malvino da (2013)
The growth of urban population in the geographic space promoted a major transformation, particularly in the relationship between society and the natural environment, emerging thus environmental problems. These perspectives motivated this study on climate change in Uberlândia (Minas Gerais), a city possessing a peculiar feature in the distribution of rainfall in the urban area and the impacts from this, that manifest reaching the various social classes in the city, regardless of its location in urban perimeter. In this sense, understanding the workings of the climate system provides a foundation for the scientific understanding that underpins human activities in different production systems, presenting a very complex behavior, its elements are distributed in various scales - from local to the global. The Convergence Zone South Atlantic (SACZ) regulates the distribution of rainfall in the Southeast, the country\'s most populous. In this context, we see the importance of this phenomenon, which regulates the distribution of precipitation, which can occur intensely, causing landslides in areas of slopes, landslides and floods. In this research, it was found that those amendments allow the occurrence of adverse events arising from the inability of urban infrastructure to absorb the waters of rain, critics mainly related to heavy rainfall and / or concentrated above 30 mm. Another focus of this study was the analysis of climate trends in the urban area of Uberlândia, with emphasis on precipitation and extreme shock. Analyses the impacts correlating with the effects of rainfall producing systems that caused impacts in the city, using as reference the newspaper Correio de Uberlândia to assess the impact on the town. It was found that climate change identified in urban areas reflect a trend of major centers, or changes in thermal patterns in the city, notably in average monthly temperatures, decrease in mean maximum, increase in mean maximum decrease in mean absolute and the absolute minimum. This irregularity was also observed in the distribution of rainfall with a tendency to increase the concentration of rainfall in 24 hours and reduction of days of rain at the beginning of the rainy season. Research regarding the action of SACZ was below expectations: totaled only 30,2% of cases from 1996. The impacts raised in the main avenues of the city (Rodon Pacheco, Professora Minervina Candida, Getúlio Vargas, João Naves de Ávila) reflect this reality. The impacts caused by rains in Uberlândia affect the entire population, regardless of social class, but the answer should emphasizes the impact: the noblest and air circulation corresponds to areas where there is a faster response to impact, as also observed in other peripheral areas, such as the region of Morumbi, Joana D Arc and São Francisco in the Eastern sector. Currently, the city requires measures that truly solve problems and not more mitigation measures. Need to have the experiences of the past three decades provide the framework for sustainable urban development, maintaining and planting trees, to expansion of areas to improve urban thermal comfort, retardation of stormwater contact with the soil, thus preventing a rapid flow.